Jua Basambuik Pohon Kelapa Ditinjau Dari Hukum Islam (Studi Analisis di Kenagarian Gunung Padang Alai Kec. V Koto Timur Kab. Padang Pariaman) - Rizda Octaviani; Adi Prawira (Saqifah: Jurnal Hukum Ekonomi Syariah, 2021)
To examine the views of Islamic law on the implementation of the coconut tree basambuik in Kenagarian Gunung Padang Alai. To discuss the problem above, the writer uses field research. Field research by observing and collecting materials from various sources related to this problem, namely by observing the symptoms studied to get an overview of the implementation of exploring juabasambuik and conducting interviews with land owners and tenants who were sampled in this study as well as various parties involved information needed. This research is a qualitative research, after the data is collected, based on the results of the analysis obtained, it was concluded that the implementation of coconut tree basambuik in Nagari Gunung Padang Alai was canceled because the pillars and conditions of ijarah were not fulfilled. The pillars and conditions that are not fulfilled are: first, the benefits that are the object of the ijarah must be fully known so that there will be no disputes in the future, both in terms of the type, nature and conditions of the goods to be rented or the work to be carried out. Second, sighat in the contract is very important because it is from the clarity of sighat that it becomes an understanding of the implementation of the ijarah, because sighat is a form of agreement from both parties to carry out the ijarah. Meanwhile, in the implementation of sighat coconut tree basambuik carried out by land owners and tenants it is not clear, the existence of gharar, namely uncertainty about the consequences of a case/transaction or, ambiguity between good and bad, for example a coconut tree falls due to lightning, it will harm the tenant while the tenant must receive compensation. profit doubled from the sale of coconut fruit, if it does not get double the profit then it is extended for one harvest and the fruit of the coconut tree as the benefit is not fully known so that disputes arise in the future.